Reconciling Human Rights And The Environment: A Proposal To Integrate The Right To Food With Sustainable Development In The 2030 Development Agenda - Juanatey, Ana García (Journal of Sustainable Development Law and Policy, 2025)
This article examines the utility of the human rights-based approach (HRBA) in tackling environmental challenges that face achievement of the right to food in coming decades. So far, such approach has been quite useful in the consideration of equity, discrimination and accountability issues. Nevertheless, the HRBA’s utility to tackle the effects of environmental degradation, natural resources depletion and climate change on food security is not that clear, as human rights law and practice has evolved in parallel with environmental concerns until recently. Therefore, this article poses the following question: is the human rights-based approach to food security sufficient to address the environmental problems and constraints that infringe directly on the right to food implementation? And, how can we integrate the needs of future generations in current human rights-based policies and deal with the tradeoffs between present and future needs? This article examines how last years’ international legal literature has portrayed the linkages between the environment and human rights, principally in relation to the right to food. Moreover, it also intends to explore possible avenues of convergence, pinpointing opportunities to connect the right to food and sustainable development in the context of the 2030 Agenda. In more concrete terms, it suggests that a greater integration between the right to food and a set of principles of sustainable development law may open new avenues for research and advocacy on the right to food.